2018
DOI: 10.1101/252858
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Detection of HPV E7 transcription at single-cell resolution in epidermis

Abstract: SummaryPersistent human papillomavirus (HPV) infection is responsible for at least 5% of human malignancies. Most HPV-associated cancers are initiated by the HPV16 genotype, as confirmed by detection of integrated HPV DNA in cells of oral and anogenital epithelial cancers. However, single-cell RNA-sequencing (scRNA-seq) may enable prediction of HPV involvement in carcinogenesis at other sites. We conducted scRNA-seq on keratinocytes from a mouse transgenic for the E7 gene of HPV16, and showed sensitive and spe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…However, this predicted interaction was absent in K14E7 LC, consistent with our previous observation that CD11b is downregulated on K14 3 10 7 APCs (Figure S1A) (Chandra et al, 2016). Similarly, CSF1R-IL-34 interactions were identified between WT LCs with WT KCs, but not between K14E7 LCs and KCs (Figure 6A) (Lukowski et al, 2018). Indeed, there was significantly lower expression of Il34 in K14E7 KCs (Figure S7B).…”
Section: Dysregulated Langerhans Cell State Is Determined By Epithelial Hyperplasiasupporting
confidence: 88%
See 1 more Smart Citation
“…However, this predicted interaction was absent in K14E7 LC, consistent with our previous observation that CD11b is downregulated on K14 3 10 7 APCs (Figure S1A) (Chandra et al, 2016). Similarly, CSF1R-IL-34 interactions were identified between WT LCs with WT KCs, but not between K14E7 LCs and KCs (Figure 6A) (Lukowski et al, 2018). Indeed, there was significantly lower expression of Il34 in K14E7 KCs (Figure S7B).…”
Section: Dysregulated Langerhans Cell State Is Determined By Epithelial Hyperplasiasupporting
confidence: 88%
“…Hyperproliferation-related effects on LCs might result from aberrant cell-cell communication. Thus, we used Cell-PhoneDB, a tool developed to predict cellular interactions from scRNA-seq datasets, based on the expression of known receptor-ligand pairs (Vento-Tormo et al, 2018), to quantify receptor-ligand pairs differentially expressed by WT or K14E7 LCs and epidermal keratinocytes (KCs), using a scRNA-seq dataset previously generated from epidermal CD45-cells from WT and K14E7 animals (Lukowski et al, 2018) (Figure S7A). Interactions of LCs with KCs were of specific interest, as these cells are subject to hyperproliferation and are the most abundant cell type in the epidermis.…”
Section: Dysregulated Langerhans Cell State Is Determined By Epithelial Hyperplasiamentioning
confidence: 99%
“…We utilized a well-characterized transgenic mouse model that expresses HPV16 E7 oncogene in basal keratinocytes, under the control of keratin 14 promoter (K14E7). This animal displays premalignant skin phenotypes (Herber et al, 1996;Lukowski et al, 2018). Contrasting with skin-expressing keratin-driven ovalbumin (OVA; Rahimpour et al, 2012) and human growth hormone (Broom et al, 2010) neo-selfantigens, K14E7 skin is not spontaneously rejected when engrafted onto naïve syngeneic hosts (Dunn et al, 1997;Matsumoto et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…These foundational studies explored cutaneous cellular composition, as well as the pathophysiologic intricacies of dermatologic disease in inflammatory and autoimmune, [15][16][17][18] malignant, 19 and infectious models. 20,21…”
Section: Historymentioning
confidence: 99%
“…Human papillomaviruses are highly prevalent and can cause benign warts and malignancies; however, the mechanism of viral-induced epidermal hyperplasia is incompletely understood. 24 scRNA-seq was first used to study viral transcriptomes in solid tissue by Lukowski et al 20 in their effort to describe this assumed linkage between human papillomavirus infection and epidermal hyperplasia. Through comparative scRNA-seq of normal and K14E7 transgenic mice, which overexpress the HPV16 E7 oncogene, they found that E7 expression is predominantly enriched in basal keratinocytes and a greater proportion of E7-positive cells express cell-cycle-and proliferation-associated genes.…”
Section: Human Papillomaviruseassociated Hyperplastic Skin Lesionsmentioning
confidence: 99%